JAEPL, Vol. 12, Winter 2006-2007 - Kristie S. Fleckenstein; Linda T. Calendrillo (Journal of the Assembly for Expanded Perspectives on Learning, 2006)
Essays Lynn Z. Bloom and Carla Hill. High Stakes Gambling in the Master Class High Stakes Gambling in the Master Class explores some of the unarticulated intangibles in a relationship between Master Teacher and Honors Student (who collaborated in writing this essay), calculated to produce a distinguished honors thesis, sometimes out of thin air, gambling, playing the hunches that will allow a gleam in the eye to metamorphose into gold on the page. Judith Beth Cohen. The Missing Body—Yoga and Higher Education. Using her own yoga practice as a basis, this author argues for more bodily involvement in learning and offers several exercises she has used to accomplish this. Carolina Mancuso. Bodies in the Classroom: Integrating Physical Literacy. This essay, based on research in Masters level classrooms for education students enrolled in a Graduate Literacy Program, addresses issues of mind-body-spirit teaching and learning.. Hildy Miller. Writing Aphrodite: Imagining a Rhetoric of Desire for a Feminist Writing Course. Reaching back to the post-Jungian goddess feminism of decades past, this essay shows how the mythical figure Aphrodite can serve as an image for an alternative rhetoric of desire in a contemporary feminist writing class. Stephanie Paterson. " Lashing Out at 'Intellectuals'": Facing Fear on Both Sides of the Desk. The author identifies stages in working through a personal attack in a student's composition. Turning toward conflict in a teacher researcher stance is a creative, self-renewing way to conduct the ongoing (often unexplored) intellectual-emotional work of writing teachers. Rich Murphy. McLuhan's Warning, Frye's Strategy, Emerson's Dream. McLuhan's Warning, Frye's Strategy, Emerson's Dream argues the vital function of literary writing in the academy. The essay maps a road from the warnings of catastrophe by Marshall McLuhan to Emerson's dream of all American citizens being poets through the writing strategies of Northrop Frye. It is argued that what one learns through literary writing is especially important during the crises that are ongoing in the West. Susan A. Schiller . Uniting Creativity and Research; A Holistic Approach to Learning. The academy needs to move closer to a holistic form of education, one that values creativity and research equally. Helen Walker. Connecting. Danina Garcia —Message from a Student Writer. Libby Falk Jones—Anger in the Teaching Life Ryan Skinnell —Connections of a First-Year Teacher Lee Roecher —Guiding the Passion. Louise Morgan —Emails to Blow Off Steam. Reviews Mary Pettice. Writing New Media: Theory and Applications for Expanding the Teaching of Composition. (Ed. Anne Frances Wysocki, Johndan Johnson-Eilola, Cynthia L. Selfe, and Geoffrey Sirc, 2004). Kerrie R. H. Farkas. Writing at the End of the World . (Richard Miller, 2005). Edward Sullivan. Field Notes on the Compassionate Life: A Search for the Soul of Kindness. (Marc Ian Barasch, 2005). Brad Lucas. (Re)Writing Craft: Composition, Creative Writing, and the Future of English Studies. (Tim Mayers, 2005).